BOD5, COD and solids removal in a facultative pond and a water hyacinth pond : a case study - Sitaramamurty, Bhamidipati; Orth, Hermann M.; I, Fude; Samorn Muttamara; The Royal Norwegian Government (Bangkok : Asian Institute of Technology, 1988)
Experiments were conducted in two stages, namely before increase of load and after increase of load on water hyacinth pond. In the first stage comparison was made between facultative pond performance and water hyacinth pond performance in removing BOD5,COD,SS and TS, where as in the second stage removal efficiency and the effect of high loading on water hyacinth was studied. Experiments were performed from October 1 5, 1 987 to December 9, 1 987 in the first stage and from December 12, 19 87 to February 28, 1 988 in the 2nd stage . The existing set of parallel oxidation ponds which are treating the wastewater from AIT campus were used in t hi s study. Hyacinth pond showed better performance compared to facultative pond even after two years of harvesting. During the period of observation the average effluent concentrations in the water hyacinth pond were 1 2, 38, 7 and 631 mg/L for BOD5, COD, SS and TS respectively, where as the corresponding values in the facultative pond were 1 4, 5 1 , 36 and 667 mg/L respectively. Mean COD loadings to the system were 83 kg/Cha. d)and 78 kg/Cha. d) for water hyacinth and facultative pond respectively. The mean mass of BOD5, COD, SS and TS were re moved at 76, 62, 85 and 26 % respectively in the hyacinth pond , where as in the facultative pond, mass BOD5, COD, SS and TS were removed at 73, 49, 33 and 24 % respectively. In the second stage when the load was 18 1 2 m3/Cha . d) as compared to the first stage load 1002 m3/Cha. d), the effluent BOD5, COD, SS and TS concentrations were 17, 47, 3 and 648 mg/L respectively. Th e mean COD loading in the second stage was 1 50 kg/Cha. d) as compared to 83 kg/( h a. d) in the first stage. The mean mass of BOD5, COD, SS and TS were removed at 76, 6 1, 85 and 35 % respectively in the second stage as compared to 76, 62, 85 and 26 % for BOD5, COD, SS and TS respectively in the first stage . This shows that the water hyacinth performance was quite good even after increase of loading.
A thesis submitted in partial fulfilment of the requirement for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1988
Keywords: Sewage lagoons; Sewage -- Purification -- Biological treatment; Hyacinths